Does Training Learners on Language Learning Strategies Have Any Effect on Language Achievement? - Okumus Ceylan, Nuray (European Journal of Sustainable Development, 2017)
This study aims to find out whether training learners on language learning strategies has an effect on foreign language learning achievement or not. The population is Kocaeli University 2013- 2014 education year Foreign Languages School students. This study is an experimental study in which randomly chosen experimental and control classes take part, and only the experimental classes were trained on language learning strategies for the defined period of time and observed until the end of the first term on their use of the language learning strategies. At the end of the first term, language learning strategies and learner autonomy surveys were conducted again as post- tests. The significant difference between the overall averages of the first term grades of beginner/ elementary level control and experimental groups shows that training students on language learning strategies may lead to better foreign language achievement, particularly in lower levels. Keywords: learner training; foreign language achievement